PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN SELF ESTEEM SISWA MELALUI PEMBELAJARAN KONTEKSTUAL BERBASIS REACT - Suji, Nur Mauliddina; Harahap, Irham Habibi (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Students' mathematical communication skills and self-esteem remain low. One learning alternative that can improve students' mathematical communication skills and self-esteem is REACT learning. The purpose of this study was to determine the improvement of students' mathematical communication skills through REACT-based contextual learning and to determine the improvement of students' self-esteem through REACT-based contextual learning. The method used in this study was quasi-experimental. The population of this study was class VIII MTs Nurul Iman Tanjung Morawa. The sample in this research was carried out using a purposive sampling technique, namely class VIII-3 as the experimental class and VIII-4 as the control class at MTs Nurul Iman Tanjung Morawa. The research instruments used consisted of a mathematical communication ability test instrument made in the form of a description (pretest-posttest), and a non-test instrument in the form of a self-esteem questionnaire. Data analysis used the t-test on pretest-posttest data via Spss for Windows version 20. From the results of the study of research data, the following conclusions were obtained: 1) the increase in mathematical communication skills of students who received the REACT-based contextual learning model was better than students who received the learning model; 2) The self-esteem of students who use the REACT-based contextual learning model is better than the self-esteem of students who use the contextual learning model